The relationship between moral judgment ability, parenting style, and perfectionism in obsessive–compulsive disorder patients: A mediating analysis - Cui, Jiacheng; Zhu, Kongmei; Wen, Jianglin; Nie, Wanjie; Wang, Dong (Frontiers in Psychology, 2023)
Guilt is an important part of obsessive-compulsive disorder. The abnormal moral cognition of obsessive-compulsive disorder patients may be closely related to their high level of guilt. The purpose of this study was to explore the development level of moral judgment in patients with obsessive-compulsive disorder and the role of parenting style and perfectionism in moral judgment development.